PARTISIPASI SISWA DALAM PELESTARIAN LINGKUNGAN DI SMAN 5 BUKITTINGGI - Nurul Hidayah; Khairani Khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to determine student participation in environmental conservation, namely at SMAN 5 Bukittinggi. This study uses a quantitative descriptive approach using an instrument in the form of a questionnaire that contains 21 items with a population of research that is students in SMAN 5 Bukittinggi. By using Random Sampling and the total number of samples that is 91 students based on sub-variables consisting of 4 sub-variables. Based on the results of research a) student participation in waste management is 76.09 which is categorized high. B) student participation in plant maintenance is 70.08% which is categorized high. c) student participation in water management is 72.53% which is categorized high. d) student participation in energy management is 65.23% which is categorized as medium. Based on the research, it was concluded that the participation of students in environmental preservation at Bukittinggi High School 5 is 70.98% which is categorized high. Keywords: Participation, Environment, Conservation.